Assessment of fecal pollution in Lake Pontchartrain, Louisiana. Issue 2 (April 2018) - Xue, Jia; Lin, Siyu; Lamar, Frederica G.; Lamori, Jennifer G.; Sherchan, Samendra
Abstract: Water quality in Lake Pontchartrain was deteriorating and recreational activities along the beach were restricted by the end of the 20th Century. A microbial source tracking (MST) study was conducted to determine the fecal contamination sources at public beach of the lake, so that effective pollution control strategies can be developed. Water samples were collected over an eight-month period at ten locations along the lake in 2016 and 2017. E. coli and Enterococcus were detected in 90.6% (culture) and 97.5% (qPCR), 95.8% (culture) and 91.8% (qPCR) of water samples from all sampling sites, respectively. Significant positive relationship between E. coli and Enterococcus results was observed for both qPCR and culture methods. HF183 marker was detected in 94.3% water samples (149 of 158), with concentrations ranging from 29.0 to 6073.5 GC/100 ml and from 129.8 to 38, 465.6 GC/100 ml in summer and winter, respectively. The results also indicate that significant rainfall events have the potential to supply considerable loads of fecal bacteria to lake waters. Further research is needed to determine the contribution of other animals to fecal contamination in the region. Highlights: All sites showed fecal pollution. Human associated genetic marker was detected in 94.3% water samples. High fecal indicator levels are associated with rainfall events.